Spectroscopic elucidation of an electron-delocalized copper–tyrosine state in heme–copper oxidases reveals its role in proton pumping - Anex Jose; Augustin Braun; Sangjin Hong; Robert B. Gennis; Edward I. Solomon (Proceedings of the National Academy of Sciences, 2026)
Heme–copper oxidases, the terminal respiratory complex in the electron transport chain, harness the energy from the reduction of dioxygen to water to pump protons across mitochondrial or bacterial membranes against a gradient to power ATP synthesis. While proton pumping in heme–copper oxidases was discovered more than four decades ago, a molecular-level understanding of the proton pumping mechanism remains elusive. Particularly, the role of the heme–copper active site, including a unique tyrosine residue covalently crosslinked to a copper ligand, remained inaccessible due to intense overlapping spectroscopic features from other redox centers in these enzymes. Here, by leveraging site-selective spectroscopic methods, we show that the active site copper and its crosslinked tyrosine directly control the proton pumping, providing the molecular mechanism underlying this process. This was achieved by experimental elucidation of the key intermediate F, formed in the first proton pumping step in heme–copper oxidases. By performing variable-temperature, variable-field magnetic circular dichroism spectroscopy on the oxo-heme center and K-edge X-ray absorption spectroscopy on the copper center of F, we find that the iron(IV)-oxo in F is ferromagnetically coupled to an electron-delocalized copper/tyrosine radical. These results show that the copper(I)-tyrosyl radical character, triggered by protonation of the heme–copper center, enables proton pumping. Furthermore, we find that the copper-tyrosyl radical character is regenerated in all four proton pumping intermediates, completing the molecular mechanism for proton pumping by the respiratory oxidase family of enzymes.